(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article presents the historical path of the “brazilianness” of operetta and “end of the year revue”, to the composition of new stage genres, in order to point out its extreme importance for the constitution of Brazilian theater. The paper presents this path in order to demonstrate the immense musical motivation of Brazilian theater of all times and how, in fact, popular musical theater was never a peripheral type of scenic art when compared to "literary" or "modern" theater, but it is the center, the motivator, perhaps the most prominent theatre genre for the conformation of the national theatre.